Identification of the maximum stress value that occur at The wing-fuselage joints at 1-G symmetrical level flight condition / Abdul Jalil A.M.H. ... [et al.] - Abdul Jalil A.M.H (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2014)
This paper described the identification of the maximum value of stress that acts at the wing-fuselage joints. The finite element models of the wing, the wing lugs and the fuselage lugs were developed. Finite Element Analyses were performed using NASTRAN finite element software. CQUAD4 and BAR2 elements were used to represent the individual structures of the wing such as the ribs and stringers are presented in detail in this paper. The applied load was based on 1-g symmetric level flight condition that was the load applied at the wing is equal to the net weight of the aircraft. Once the load distribution acting at the wing have been calculated and applied, reaction forces at the nodes representing the wing lugs are obtained and these values are applied to the lug models where the maximum stress value acting at the lugs was obtained. This stress value can be further used for fatigue calculations.